Antara Idealisme dan Praktek Masyarakat dalam Pembagian Harta Waris - Muhammad Al Faruq (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
The Qur'an has set on how to divide the inheritance, warits, and conditions as warits, and things that in detail discuss the inheritance. Ideally, the provisions that have been determined by the Qur'an should be carried out as a form of a Muslim's slavery to its Lord's teachings. However, due to the various factors covered, the provisions are not implemented, so the understanding of the existence of Islamic inheritance is as if only a sequence of rules without practice. Therefore, the authors do a study of the factors affecting the injustice of the inheritance of Islam in addition to the problem of the passage of the estate between men and women. Conclusion obtained that the inheritance of Islam law is not in the matter of the division of the inheritance between the sons and women so that there is a mismatch between the doctrine of Islamic inheritance law with the practice in society because Several factors, namely: 1) still the public with the existence of customary law used in the division of inheritance. 2) The existence of the assumption or understanding that the division of property in the inheritance law of Islam is unfair, with the concept of 2:1. 3) There is still too much that underestimate the urgency of Islamic inheritance to assume that the internal problems in terms of inheritance can be resolved through a family principle alone.